Not all Septic Shock is due to infection ! - V S V Prasad (Wolters Kluwer Medknow Publications, 2014)
We describe a case of Atypical Kawasaki disease presenting as septic shock in a 3 month old male baby. Atypical Kawasaki disease should be considered in all infants with unexplained fever for > 5 days associated with 2 or 3 of the principal clinical features of Kawasaki disease . Because young infants may present with fever and few clinical features, echocardiography should be considered in any infant aged <6 months with fever of > 7 days' duration, laboratory evidence of systemic inflammation, and no other explanation for the febrile illness